So we are given that \[x^2+y^2-x-2kxy=0.\]
Write \(x=a^2b\) with \(b\)square-free. Then
\[a^4b^2+y^2-a^2b-2ka^2by=0,\] so \(a^2\mid y^2\) and \(a\mid y\), say \(y=ac\)
Then \[a^2b^2+c^2-b-2kabc=0,\] so \(b\mid c^2\) and as \(b\) is square-fee in fact \(b\mid c\), say \(c=bd\).
Then
\[a^2b+bd^2-1-2kabd=0,\]
so \(b\mid 1\).
Assume \(b=-1\). Then we have
\[ a^2+d^2=2kad-1.\]
As the right hand side is odd, exactly one of \(a,d\) must be odd, the other even. But then the right hand side is \(\equiv -1\pmod 4\) and the left is \(\equiv +1\pmod 4\)
We conclude \(b\ne -1\), hence \[b=+1\] and \[x=a^2.\]
and the proof is completed

Thanks for taking your time to it, but do you mind giving some clarification.How do you know that x is not prine or a product of primes per example 5 ,6,15,13 etc and cannot be written as you stated in your solution. Forgive me if im missing some important clue. Also i forgot to state that x and y are POSITIVE INTEGERS. Disregard this reply if you were based heavily on this conditiom.

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestSo we are given that \[x^2+y^2-x-2kxy=0.\] Write \(x=a^2b\) with \(b\)square-free. Then \[a^4b^2+y^2-a^2b-2ka^2by=0,\] so \(a^2\mid y^2\) and \(a\mid y\), say \(y=ac\) Then \[a^2b^2+c^2-b-2kabc=0,\] so \(b\mid c^2\) and as \(b\) is square-fee in fact \(b\mid c\), say \(c=bd\). Then \[a^2b+bd^2-1-2kabd=0,\] so \(b\mid 1\). Assume \(b=-1\). Then we have \[ a^2+d^2=2kad-1.\] As the right hand side is odd, exactly one of \(a,d\) must be odd, the other even. But then the right hand side is \(\equiv -1\pmod 4\) and the left is \(\equiv +1\pmod 4\) We conclude \(b\ne -1\), hence \[b=+1\] and \[x=a^2.\] and the proof is completed

Log in to reply

Oh that's very nice! Much simpler than the approach I would have taken.

Log in to reply

Thanks for taking your time to it, but do you mind giving some clarification.How do you know that x is not prine or a product of primes per example 5 ,6,15,13 etc and cannot be written as you stated in your solution. Forgive me if im missing some important clue. Also i forgot to state that x and y are POSITIVE INTEGERS. Disregard this reply if you were based heavily on this conditiom.

Log in to reply

See Vieta Root Jumping .

Log in to reply

Thanks,sir

Log in to reply

Can you please give the main idea?I have been trying it for 3 days.

Log in to reply

Also , 8 is a factor of 16 but 8 is not a factor of 4 and 8 is square free.

Log in to reply